FACEBOOK GROUP ON TEACHING AND IMPROVING WRITING: STUDENTSâ PERCEPTIONS - Sholah, Hanif Maulaniam (Jurnal al Hikmah, 2016)
Teaching and learning English generally occur in classroom. However, actually it can occur outside classroom like independent learning where students prefer their own way to learn. Recently, in this modern era, technology has spread all over the world and be used by any age of people either worker or learners. For learners, technology is good equipment that can help them to learn. One feature in technology which is generally used by many students is Facebook. They use Facebook more often than learning lesson in classroom. In this case, researcher tried to investigate the use of Facebook in learning English and to know how effective it is. This research was conducted in IAI Al-Qolam which the participants were 30 students. The researcher here was a lecturer who observed and guided students to follow the research program. Participants were lead to participate actively in FB group called as EDG (English Department Group). In this group, researcher as well as Lecturer guided students to discuss any interesting topic by sharing any articles, made some writings or comment their friends writing. Students perceptions were measured by using 13 questionnaires related to the students usage of Facebook group. As a result, students enjoy discussing and learning using FB group. It is shown from their comments written on their FB group wall. The finding shows that Facebook group is an effective tool for students to improve their writing skill. This finding is benefitful for teachers as a guide for using ICT for teaching and learning process